Photography and the Non-Place - Brogden, Jim. author. aut Link
XX, 218 p. 37 illus., 28 illus. in color.
Keywords: This book presents a critical and aesthetic defence of “non-place” as an act of cultural reclamation. Through the restorative properties of photography, it re-conceptualises the cultural significance of non-place. The non-place is often referred to as “wasteland”, and is usually avoided. The sites investigated in this book are located where access and ownership are often ambiguous or in dispute; they are places of cultural forgetting. Drawing on the author’s own photographic research-led practice, as well as material from photographers such as Ed Ruscha, Joel Sternfeld and Richard Misrach, this study employs a deliberately allusive intertexuality to offer a unique insight into the contested notions surrounding landscape representation. Ultimately, it argues that the non-place has the potential to reveal a version of England that raises questions about identity, loss, memory, landscape valorisation, and, perhaps most importantly, how we are to arrive at a more meaningful place. .